Reimagining Orientalism for Global Peace in the Changing Context - Niranjan Ojha (ABM: International Journal of Administration, Business and Management, 2024)
Orientalism is still relevant today, even in its changing manifestations, in a world defined by globalization, technological innovation, and altering geopolitical environments. Orientalism was first used by Edward Said to criticize how the West saw the East, but term has since expanded to include a wider range of power relationships, cultural narratives, and perspectives. This article seeks to reinterpret orientalism in the context of world peace by examining its ramifications, difficulties, and potential benefits for promoting mutual understanding and collaboration amongst various cultural and societal groups. Utilizing multidisciplinary viewpoints from postcolonial studies, international relations, and cultural theory, this piece puts forth a nuanced interpretation of orientalism that recognizes its complicated past while arguing for its transformative capacity to foster communication, compassion, and unity in a globalized society. The study employs qualitative approaches such as in-depth interviews, discussions with historians, scholars, and university instructors, as well as library research.